Antioxidant Properties of Pistacia khinjuk Accelerate Healing of the Experimental Achilles Tendon Injury in Rabbits - HR Moslemi; Hossein Fazel (Institue of Medicinal Plants, ACECR, 2017)
Background: Delayed tendon healing and tendon adhesions are still found to be among the complications that occur most often after tendon repair. Pistacia khinjuk is one of the three species of Pistacia growing in Iran. Objective: In this study, the role of local injection of ethanolic extract of P. khinjuk was evaluated in healing of the experimental Achilles tendon injury in rabbits. Methods: Nine adult male white New Zealand rabbits were anesthetized and a partial thickness tenotomy was created on both hindlimbs. P. khinjuk extract and normal saline were injected daily to the treatment and control groups, respectively for three days post-operatively. Results: Based on the findings, on days 14, 28 and 42 after the injury, the healing rate in P. khinjuk treated groups were higher than control groups in tendon sections significantly (P ≤ 0.05). In summary, results of this study showed that the application of P. khinjuk extract can improve the healing process of damaged Achilles tendon in rabbits. Conclusion: Significant differences between the treatment and control groups in the current study suggest that the application of P. khinjuk extract can improve the healing process of damaged Achilles tendon.